Developing writing skills for students at Kien Tho secondary school through fairy tales. M.A. Thesis Linguistics : 60 14 01 11 - Đàm, Thị Thúy (ĐHNN, 2017)
This study has been conducted to display how effective fairy tales can assist to consolidate students’ knowledge of the English language as grammar and vocabulary and to promote their self-confidence and creative writing skills. Besides that, the author also mentions stories as a good motivation to raise students’ interest in writing tasks.